Determinan Penerimaan Vaksinasi COVID-19 pada Masyarakat Aceh Tahun 2021 - Fitriani Agustina; Said Taufiq; M. Jamil Fauzi; Sulaiman Sulaiman (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the determinants associated with receiving the COVID-19 vaccination in Aceh. This research method uses a quantitative analytical approach with a cross-sectional design. The study's results found a significant relationship between knowledge and acceptance of the COVID-19 vaccine (0.001). Meanwhile, for other variables, there was no relationship between comorbid status (1,000), anxiety (0,237), and social support (0,605) with receiving the COVID-1 vaccine. It is concluded that public knowledge needs to be increased because it positively impacts the acceptance of the COVID-19 vaccination. Keywords: COVID-19, Community Acceptance, Vaccination